Ensemble‐based ADME–Tox profiling and virtual screening for the discovery of new inhibitors of the Leishmania mexicana cysteine protease CPB2.8ΔCTE. (10th November 2017) - Scala, Angela; Rescifina, Antonio; Micale, Nicola; Piperno, Anna; Schirmeister, Tanja; Maes, Louis; Grassi, Giovanni
Abstract : In an effort to identify novel molecular warheads able to inhibit Leishmania mexicana cysteine protease CPB2.8ΔCTE, fused benzo[ b ]thiophenes and β, β ʹ ‐triketones emerged as covalent inhibitors binding the active site cysteine residue. Enzymatic screening showed a moderate‐to‐excellent activity (12%–90% inhibition of the target enzyme at 20 μm ). The most promising compounds were selected for further profiling including in vitro cell‐based assays and docking studies. Computational data suggest that benzo[ b ]thiophenes act immediately as non‐covalent inhibitors and then as irreversible covalent inhibitors, whereas a reversible covalent mechanism emerged for the 1, 3, 3ʹ‐triketones with a Y‐topology. Based on the predicted physicochemical and ADME–Tox properties, compound2b has been identified as a new drug‐like, non‐mutagen, non‐carcinogen, and non‐neurotoxic lead candidate. Abstract : Fused benzo[ b ]thiophenes and β, β′‐triketones as electrophilic warheads binding CPB2.8. Computational data show irreversible and reversible covalent inhibition, respectively. Enzymatic screening show 12%–90% inhibition of the target enzyme at 20 μm .